The Effect of Probiotic Supplementation on Growth Performance and Feed Efficiency in Broiler Chickens - Arian Gufron; Rafael Opazo (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
The poultry industry faces increasing pressure to improve productivity while reducing the use of antibiotic growth promoters. Probiotics have emerged as a promising alternative to enhance growth performance and feed efficiency in broiler chickens. This study aims to analyze the effect of probiotic supplementation on growth performance and feed efficiency in broilers based on experimental observations supported by previous empirical findings. The research used a quantitative experimental approach involving broiler chickens divided into control and treatment groups receiving probiotic supplementation in feed. Growth performance parameters included body weight gain, feed intake, and feed conversion ratio. Data were analyzed using descriptive and comparative statistical methods. The results showed that probiotic supplementation significantly improved growth performance and feed efficiency compared to the control group. Broilers receiving probiotics showed higher body weight gain and improved feed conversion ratio. These findings are consistent with previous studies reporting that probiotic strains such as Lactobacillus and Bacillus improve nutrient digestibility and intestinal microflora balance. The study concludes that probiotic supplementation is an effective nutritional strategy to enhance broiler productivity and reduce dependence on antibiotics in poultry production systems.